Diamond turning of thin aluminium surfaces with grooved base - Ramalingam Vigneshwaran (2013)
The parameter that has a major control over the performance of the optical components is its surface texture. Single point diamond turning is one of the most sought after machining process using which non-ferrous metals and polymers can be turned to obtain very good optical surface finish quality with very less amount of surface roughness and inaccuracies. There are many factors which affect this roughness and the surface texture of the workpiece material such as the feed rate, depth of cut, tool geometry etc. Apart from these factors, any difference in the geometry of the resting surface of the workpiece, i.e, the surface opposite to the surface being machined might also affect the quality of the resulting machined surface to a significant amount in case of thin workpieces. This particular phenomenon has been taken into main focus in this dissertation work. Workpiece made from aluminium alloy material is turned using the single point diamond turning process. Different geometrical grooves have been intentionally made on the other side of the workpiece before machining. After reducing the workpiece thickness below 500J.lm by turning to optical quality, the surface is studied using zygo interferometer and talyscan surface profiler. The resulting surface is expected to have bumps (peaks and valleys) corresponding to the grooves, thereby